PENGEMBANGAN LKPD BERBASIS PENDEKATAN STEM PADA MATERI ENERGI DI KELAS IV SD/MI - R, Salma Fauziah; Carlian, Yayan; Mahmud, Muhammad Rifqi; Rahmaniar, Andinisa; Rohimah, Siti Maryam (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
This research aims to develop Student Worksheets (LKPD) based on the STEM approach on energy material for 4th-grade elementary/middle school students in order to support the implementation of the Independent Curriculum. The STEM approach was chosen because it is considered effective in integrating science, technology, engineering, and mathematics to enhance 21st-century skills such as critical thinking, creativity, collaboration, and problem-solving. The method used is qualitative research with a Research and Development (RnD) approach, adapting the ADDIE model which consists of the stages of analysis, design, and development. The development process was carried out through learning needs analysis, the design of LKPD, and validation by experts in content, media, language, and STEM. The research results show that the developed LKPD has valid quality and can be applied in learning to enhance students' understanding of energy material with a contextual and interactive approach.